Callitriche aucklandica Mason 1959 - Lansdown, Richard V. (Zenodo, 2022)
2. Callitriche aucklandica Mason (1959: 307). Type: — NEW ZEALAND. AUCKLAND ISLANDS. Auckland I., J.B. Hair s.n. , Nov. 1954. (Holotype: CHR 89341, isotypes: CHR 89342!, CHR 89344!). Description: —Stem and leaf scales present. Leaf bases connate. Lingulate leaves unknown; expanded submerged or floating leaves unknown; leaves of terrestrial plants slightly fleshy 3.7–8.0 mm long × 1.2–4.0 mm wide, 3-nerved, occasionally with short free veins, blade and petiole poorly differentiated. Flowers solitary or sometimes ♂ and ♀ together. Bracts caducous, 0.3 mm long. Styles persistent, erect, 2.0– 2.5 mm long. Filament erect, <9 mm long; anthers, 0.6–0.8 mm long × 0.5–0.8 mm wide, number of locules unknown; pollen yellow. Fruit not strumose, subsessile, wider than high, dark brown, 1.1 mm long × 1.2–1.3 mm wide, narrowly winged throughout. Illustrations: — Figures 7 (a–b) and 7A(a–b) in Mason 1959. Fig. 1b. Recognition: — C. aucklandica can be distinguished from all other Callitriche species except C. antarctica by the fleshy leaves with connate bases. C. aucklandica differs from C. antarctica in the narrow wing on the fruit. Distribution: —Native. Callitriche aucklandica is endemic to the Auckland Islands, where it has been recorded from Dundas Island (Falla et al . 1979), Ewing Island and Auckland Island but its occurrence on the other islands cannot be discounted. Habitats and Ecology: — C. aucklandica is described as common in wet ground at low altitude (Johnson and Campbell 1975), it occurs in coastal to montane areas on exposed ground, in pools and on sodden peat, in heavy shade under both young and mature Olearia Moench (1802: 254) forest, as well as in Metrosideros umbellata Cavanilles (1797: 20) mixed forest and with Stellaria media (von Linné) Vill. (1789: 615) between Poa foliosa tussocks (Falla et al . 1979, Johnson and Campbell 1975, Webb et al . 1988, Lee et al. 1991). It often occurs near bird colonies and in areas recovering after use by sea lions but also on exposed mud within forest and scrub ...